DESIGNING ENGLISH LANGUAGE TEACHING MATERIAL FOR PHYSICS EDUCATION DEPARTMENT STUDENTS AT UIN ALAUDDIN MAKASSAR: OPTIC UNIT (International Conference on Social and Islamic Studies, 2022)
Materials play important role in ELT. The preliminary data showed that there was no primary module included in the learning package and the English course material was irrelevant to their major (not an ESP material). This study aims to design the "Optic" topic of English Language Teaching Material for Physics Education Department at UIN Alauddin Makassar. This study applied Research and Development Method with ADDIE Model (analysis, design, development, implementation, and evaluation). In order to analyze the data, this study used two research instruments, which are the document of Need Analysis Data and Evaluation Checklist. The subject of the research is the researcher and two validators from English Education Department. The data collection procedures included analysing, designing, developing and evaluating. The findings of this study demonstrate that the researchers have designed prototype syllabus as a blue print to design module. In designing module, the researchers applied three steps: selecting from existing materials related to the topic, writing our own materials related to the topic and modifying existing materials related to the materials.  Additionally, the evaluation checklist's results shows that the Optic units (syllabus and the module) have been carefully designed that fulfilling the needs of the students. The product is suggested particularly to use by lecturers in English Language Teaching classroom. It can also be used as a preliminary step for the future researcher to try out the Optic unit of the module in implementation stage.